Evolution of Performance Engineering: From Desktop to Wearables - A Comprehensive Analysis of System Optimization Across Device Types - Sayanna Chandula; Jyothi Prakash Reddy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the evolution and fundamentals of performance engineering across various device types, from desktop computers to modern wearable technology. This article examines core objectives, key metrics, and emerging trends in performance optimization while highlighting the increasing complexity of hardware-software integration challenges. This article delves into the transformation of performance engineering methodologies, emphasizing the critical role of power efficiency, system reliability, and resource management in modern computing systems. This article analyzes the impact of artificial intelligence integration, next-generation connectivity, and extended reality technologies on performance engineering practices. Through detailed examination of testing methodologies and optimization techniques, the article demonstrates how performance engineering has adapted to meet evolving user expectations and technological capabilities. This article provides insights into the symbiotic relationship between device evolution and performance optimization, highlighting the importance of balanced approaches in addressing both immediate user needs and long-term technological sustainability.